2014
DOI: 10.1007/s00216-014-7732-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a DNA-cleaving DNAzyme and PCR into a simple sensor for zinc ion detection

Abstract: The development of a simple sensor (9NL27-Zn) based on DNAzyme and PCR and aimed at the detection of low concentrations of zinc (II) ions is described. A specific Zn(II)-dependent DNAzyme (9NL27) with DNA-cleaving activity was employed. In the presence of zinc (II), the DNAzyme hydrolyzed DNA substrate into two pieces (5' and 3' fragments), forming 3'-terminal hydroxyl in the 5' fragment and 5'-phosphate in the 3' fragments. Subsequently, the 5' fragment left the DNAzyme and bound a short DNA template. The 5' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[38] This DNAzyme was later used as a sensor for Zn 2 + detection. [94] Gu and Breaker reported a new selection method using a circular library and obtained a few small DNA-cleaving DNAzymes (Figure 5A). [37] IÀ R1 is a self-cleaving DNAzyme, while IÀ R3 can be separated into a substrate strand and an enzyme strand.…”
Section: Dna-cleaving Dnazymesmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] This DNAzyme was later used as a sensor for Zn 2 + detection. [94] Gu and Breaker reported a new selection method using a circular library and obtained a few small DNA-cleaving DNAzymes (Figure 5A). [37] IÀ R1 is a self-cleaving DNAzyme, while IÀ R3 can be separated into a substrate strand and an enzyme strand.…”
Section: Dna-cleaving Dnazymesmentioning
confidence: 99%
“…Later, the group found that by just mutating two nucleotides in the original 10MD5, the requirement of Mn 2+ can be omitted and activity was achieved with Zn 2+ alone [38] . This DNAzyme was later used as a sensor for Zn 2+ detection [94] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of these ions is related to their presence in Sarthe River Basin of "Le Mans" region [32]. Several receptors have been investigated for zinc ions detection, mainly ion imprinted polymers [33][34][35], DNA [36], aptamers [37], self-assembled monolayers (SAM) [38,39], enzymes [40,41], and molecular cages [42][43][44][45]. Herein, we have chosen to functionalize the sensitive zone of the 104 MHz and 208 MHz SAW sensor with 9-{[4-({[4-(9 anthrylmethoxy) phenyl]sulfanyl} methyl)]methyl] anthracene (TDP-AN).…”
Section: Introductionmentioning
confidence: 99%
“…It can bind with metal ion specifically in a short time, and then cleave the complementary single‐stranded DNA (CS‐DNA) at a specific site , which can overcome the long analysis time using aptamer‐based biosensors, and poor stability of protease‐based biosensors. Up to now, metal ions including Na + , Ag + , Hg 2+ , Pb 2+ , Cu 2+ , Ca 2+ , Zn 2+ , Cd 2+ , Cr 3+ have been detected using DNAzymes . A variety of DNAzyme‐modified biosensors for Pb 2+ detection were reported.…”
Section: Introductionmentioning
confidence: 99%